Revealing the Meaning of Indonesian Cryptocurrency Investment Decisions Based on Mental Accounting: A Phenomenological Study - Ginting, Rafles; Crystopher, David; Yunita, Khristina (Jati: Jurnal Akuntansi Terapan Indonesia, 2023)
Mental accounting is in the form of a series of cognitive operations used by individuals to code, categorize and evaluate their financial activities which is a development of prospect theory, where each individual has a tendency to classify money into certain groups according to a criterion. From this background, the researcher has the main objective of this study, which is to find out the meaning of mental accounting for the investment decisions of Indonesian cryptocurrency investors. Mental accounting may have some kind of meaning on investment decisions, especially cryptocurrencies, so this study aims to find out what leads to mental accounting in Indonesian cryptocurrency investors. This research method uses a qualitative phenomenological approach with in-depth interview primary data. The results show that the application of mental accounting helps investor in managing portfolios and finances, but anomalies in mental accounting and prospect theory can make investors make high-risk investment decisions and are prone to causing losses.